Trust in healthcare providers among Chinese immigrants living with hepatitis B virus in Australia: A qualitative study. Issue 11 (17th August 2022) - Jin, Defeng; Brener, Loren; Treloar, Carla
Abstract: Despite the importance of trust in healthcare settings, there remains a paucity of evidence on the role it plays in patient–provider relationships and healthcare outcomes among people living with hepatitis B virus (HBV). International evidence suggests that Chinese immigrants living with HBV experience inequitable access, outcomes and treatment quality in chronic hepatitis B (CHB) health care. This study explores individual trust in healthcare providers and its impact on health‐seeking behaviours and health outcomes among Chinese people living with HBV in Australia. A total of 16 participants were recruited from the Chinese community in Sydney and Melbourne and participated in semi‐structured interviews. The data were analysed within a conceptual model of trust that contains five dimensions: fidelity, competence, honesty, confidentiality and global trust. The data shows how trust in physicians was formed and influenced by factors including patient–provider interactions, historically relevant experiences, health and illness beliefs and systemic barriers. While the research confirms prior findings on the impact of trust and mistrust, showing an association between low trust and treatment nonadherence, it also generates fresh insights by examining what leads to mistrust and the role of trust in shaping participants' healthcare outcomes. Findings suggest that by treating patients with respect and dignity, improving interpersonal skills and cultural competency, having open discussion on complementary and alternative medicine (CAM) treatment and protecting private information, physicians can increase patients' trust. The findings will contribute to efforts to address HBV as a health priority and increase patients' trust in healthcare providers among Chinese immigrants living with HBV.